Toxicant exposure and the developing brain: A systematic review of the structural and functional MRI literature. (January 2023) - Fowler, Carina H.; Bagdasarov, Armen; Camacho, Nicolas L.; Reuben, Aaron; Gaffrey, Michael S.
Abstract: Youth worldwide are regularly exposed to pollutants and chemicals (i.e., toxicants) that may interfere with healthy brain development, and a surge in MRI research has begun to characterize the neurobiological consequences of these exposures. Here, a systematic review following PRISMA guidelines was conducted on developmental MRI studies of toxicants with known or suspected neurobiological impact. Associations were reviewed for 9 toxicant classes, including metals, air pollution, and flame retardants. Of 1264 identified studies, 46 met inclusion criteria. Qualitative synthesis revealed that most studies: (1) investigated air pollutants or metals, (2) assessed exposures prenatally, (3) assessed the brain in late middle childhood, (4) took place in North America or Western Europe, (5) drew samples from existing cohort studies, and (6) have been published since 2017. Given substantial heterogeneity in MRI measures, toxicant measures, and age groups assessed, more research is needed on all toxicants reviewed here. Future studies should also include larger samples, employ personal exposure monitoring, study independent samples in diverse world regions, and assess toxicant mixtures. Highlights: We conducted a systematic review of MRI studies on toxicant exposure and youth brain structure and function. 9 toxicant classes were reviewed, including air pollution, metals, pesticides, flame retardants, phthalates, and bisphenols. Most studies examined air pollution or metals, assessed exposures prenatally, and conducted imaging in late middle childhood. Most studies took place in Europe or North America, drew samples from existing cohort studies, and were published since 2017. More research on all toxicant classes reviewed here is needed.